In vitro fermentation of κ-carrageenan oligosaccharides by human gut microbiota and its inflammatory effect on HT29 cells - Yujiao Sun; Xiangyi Cui; Mengmeng Duan; Chunqing Ai; Shuang Song; Xuefeng Chen (Journal of Functional Foods, 2019)
In vitro fermental behaviors and colonic inflammation of κ-carrageenan oligosaccharides (KO3 and KO6) obtained from simulated gastric digestion were investigated. With the proceeding of fermentation, κ-carrageenan oligosaccharides were readily degraded, exerting a notable impact on production of SCFAs and composition of gut microbiota. Both KO3 and KO6 significantly promoted pro-inflammatory bacteria Prevotella, while inhibited anti-inflammatory bacteria Bacteroides and Parabacteroides. Notably, fermental behavior of KO3 with larger degrees of polymerization (DPs) and KO6 with smaller DPs showed different responsible for fermentation, of which KO3 improved SCFAs production and highly increased the growth of Bifidobacterium and Lactobacillius, while KO6 reduced SCFAs production and enormously enhanced the abundance of mucin-producing bacteria Prevotellaceae. Associated with inflammatory effect on HT29 cells, KO6 fermental supernatants more promoted the secretions of IL-1β, TNF-α, SIgA and mucin2, hinting that smaller κ-carrageenan oligosaccharides might pose stronger inflammation. The results can be helpful for understanding the safety of κ-carrageenan oligosaccharides.